Resident memory CD4+ T lymphocytes mobilize from bone marrow to contribute to a systemic secondary immune reaction. Issue 5 (14th March 2022) - Cendón, Carla; Du, Weijie; Durek, Pawel; Liu, Yuk‐Chien; Alexander, Tobias; Serene, Lindsay; Yang, Xinyi; Gasparoni, Gilles; Salhab, Abdulrahman; Nordström, Karl; Lai, Tina; Schulz, Axel R.; et al.
Abstract: Resident memory T lymphocytes (TRM ) of epithelial tissues and the Bm protect their host tissue. To what extent these cells are mobilized and contribute to systemic immune reactions is less clear. Here, we show that in secondary immune reactions to the measles‐mumps‐rubella (MMR) vaccine, CD4 + TRM are mobilized into the blood within 16 to 48 h after immunization in humans. This mobilization of TRM is cognate: TRM recognizing other antigens are not mobilized, unless they cross‐react with the vaccine. We also demonstrate through methylome analyses that TRM are mobilized from the Bm. These mobilized cells make significant contribution to the systemic immune reaction, as evidenced by their T‐cell receptor Vβ clonotypes represented among the newly generated circulating memory T‐cells, 14 days after vaccination. Thus, TRM of the Bm confer not only local, but also systemic immune memory. Abstract : The contribution of tissue‐resident memory T lymphocytes to systemic immunity has been a matter of debate. This study demonstrates that resident memory T lymphocytes are rapidly mobilized from the human Bm in secondary systemic immune reactions, and essentially contribute to them.